2010
DOI: 10.1590/s0100-69162010000200017
|View full text |Cite
|
Sign up to set email alerts
|

Cobre e zinco no material percolado e no solo com a aplicação de água residuaria de suinocultura em solo cultivado com soja

Abstract: O objetivo deste trabalho foi avaliar possíveis efeitos da aplicação de taxas de água residuária de suinocultura (ARS), quanto às concentrações de cobre e zinco, tanto no solo quanto na água percolada de lisímetros de drenagem, durante o ciclo da cultura da soja. O experimento foi conduzido em ambiente protegido, onde havia 24 lisímetros de drenagem. Semeou-se soja cultivar CD 202, e foram aplicadas ARS nas seguintes dosagens: 0; 100; 200 e 300 m³ ha-1 no ciclo, combinadas com duas adubações na semeadura (com … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
20
0
16

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(40 citation statements)
references
References 16 publications
4
20
0
16
Order By: Relevance
“…of the fourth leaf developed to the end of the crop cycle, called as dolled up in case of the babycorn, totaling seven observations in which plant height (EP), vertical distance between soil surface and the highest part of the plant, number of leaves developed per plant (NF P -1 ), leaf area (LA) length by width of leaf product multiplied by a 0.75 factor (Stickler et al, 1961), leaf area index (LAI) -ratio between photosynthetic active leaf area and the land surface area occupied by the plant, absolute growth rate (AGR) -ratio between height and time between two successive samplings.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…of the fourth leaf developed to the end of the crop cycle, called as dolled up in case of the babycorn, totaling seven observations in which plant height (EP), vertical distance between soil surface and the highest part of the plant, number of leaves developed per plant (NF P -1 ), leaf area (LA) length by width of leaf product multiplied by a 0.75 factor (Stickler et al, 1961), leaf area index (LAI) -ratio between photosynthetic active leaf area and the land surface area occupied by the plant, absolute growth rate (AGR) -ratio between height and time between two successive samplings.…”
Section: Methodsmentioning
confidence: 99%
“…The determination of N, P, K, Ca, Mg, S, Cu, Zn, Mn and Fe followed the methodology proposed by Tedesco et al (1995) The average contents (Table 3) of N and K are below levels considered adequate for maize (27.5 to 32.5 g kg -1 and 17.5 to 22. 5 g kg -1 , respectively) and the nutrients P, Ca, Mg and S are much higher than the appropriate values (2.5 to 3.5, 2.5 to 4.0, 2.5 to 4,0 and 1.0 to 2.0 g kg -1…”
Section: Foliar Concentrations Of Macro and Micronutrientsmentioning
confidence: 99%
See 1 more Smart Citation
“…No significant differences were observed for any form of NO 3+ NO 2+ in the leachate, both for SW and MF (Table 5). DAUDÉN & QUÍLEZ (2004), MAGGI et al (2011) andSMANHOTTO (2008) in their experiments with SW found no significant differences in the concentrations of these elements in the leachate either.…”
Section: It Is Observed Inmentioning
confidence: 82%
“…Authors like AITA & GIACOMINI (2008), BERWANGER et al (2008), CAOVILLA et al (2010 and SAMPAIO et al (2010a) who evaluated the negative impacts of the swine wastewater application in soil, such as fertility problems and toxicity resulting from accumulation of ions in soil. Other authors also claim that the manure application is prone to surface and groundwater contamination due to surface and vertical displacement of these ions accumulated in soil (PRIOR et al, 2009;SAMPAIO et al, 2010b;SMANHOTTO et al, 2010;MAGGI et al, 2011;LUCAS et al, 2013).…”
Section: Introductionmentioning
confidence: 99%